Uwarunkowania komunikacji werbalnej i niewerbalnej w marketingu międzynarodowym - Skulski, Przemysław (Problems of Verbal and Nonverbal Communication in International Marketing, 2008)
Analysis of socio-cultural phenomena such as verbal and non-verbal communication is a challenging task, due to variety of factors in play, including different interpretations of the concept of culture and immeasurability of socio-cultural elements. Language is a basic tool of interpersonal communication. As demonstrated in everyday practice, ignorance of the language common for all market participants may negatively influence economic results and company image. It may also prove disadvantageous in international negotiations and marketing efficiency. Linguistic problems may result from errors in translation of product names and marketing slogans. Companies catering for global markets constantly face the challenge of providing suitable names for their products. Activities on global markets are also strongly influenced by non-verbal communication, especially kinestetics (gestures). Problems of such nature are decisive both on the level of negotiations with foreign partners, and during consecutive contractual meetings. Examples of non-verbal communication problems include misinterpretation of various gestures and behaviours in different countries and cultural settings.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 124-131